Fusarium pseudocircinatum Causing Stunting and Malformation of Sunflower Plants in Brazil - Farias, Otília (2023)
Sunflower (Helianthus annuus L.) is among the main oleaginous crops used in Brazil. During January 2017, at CCA/UFPB laboratory and green- houses (Areia, Brazil, 6°589120S; 35°429150W), we observed various sun- flower seeds (cultivar Olisun 3, 2017 to 2018 crop) highly infested with Fusarium. Those seeds were from crops in the municipality of Alagoinha, Para ́ıba, Brazil (06°579000S; 35°329420W), supplied by Empresa Brasileira de Pesquisa Agropecua ́ria/EMBRAPA. The emerged seedlings from these seeds were also contaminated, with 5 to 26% of them exhibiting stunting and malformation. Fusarium strains were isolated from symptomatic plants, and a single spore was used to grow pure colonies on potato dextrose agar (PDA) and synthetic nutrient-poor agar (SNA) media. Mycelia of PDA colonies were floccose and dense, varying from yellow to orange. Fungal colonies developed aerial mycelium, producing orange pigments. On SNA, hyaline macroconidia were 2.9 to 4.1 × 32.4 to 65.0 μm, slightly falcate, and with three to six septa. Oval microconidia, measuring 2.4 to 3.6 × 5.1 to 9.0 μm, were abundant in false heads forming on monophialides. Chlamydospores were absent. Sterile hyphae were rarely formed. Collectively, the morpho- logical features corresponded to species of the Fusarium fujikuroi species complex (Leslie and Summerell 2006). To assure the species identity, we sequenced the elongation factor 1a region of two representative isolates (F2 and F3, GenBank accession nos. MZ666934 and MZ666935, respectively) and compared them to other Fusarium species found at Fusarium-ID and GenBank databases. Subsequently, we performed a maximum likelihood phylogenetic analysis including previously published sequences (Nicolli et al. 2020). Both isolates exhibited 100% similarity with Fusarium pseudocircinatum (MN386745), and clustered with its ex-type at 100% bootstrap values. The isolates were then grown on PDA amended with manitol to adjust the os- motic pressure to !1.0 MPa at 25 ± 2°C for 7 days (Sousa et al. 2008). A total of 100 disinfested sunflower seeds (cultivar Olisun 3, 2018 to 2019 crop) were distributed over the colonies and 48 h later they were sown on sterile substrate maintained inside a greenhouse. About 30 days after in- oculation,theemergedplantsexhibitedsymptomsofstuntingandmalfor- mation (60%); controls were healthy. F. pseudocircinatum was reisolated from the symptomatic plants, completing Koch’s postulates, and identified based on the above morphological and molecular methods. This test was performed twice. Fusarium pseudocircinatum is a broadly distributed and ecologically diverse species that infects several wild and cultivated plants. For instance, it was reported on seeds of the wild ‘Peroba Rosa’ (Aspidosperma polyneuron Muell. Arg.) in Brazil (Mazarotto et al. 2020). Infection of sun- flowers may cause plant stand failures, resulting in yield and economic losses for Brazilian growers. The correct identification of any pathogen, especially a gener- alist one such as F. pseudocircinatum, is crucial to develop efficient management strategies. To our knowledge, this is the first report of F. pseudocircinatum causing stunting and malformation of sunflower plants in Brazil.